INTEGRATION OF FAMILY COACHING AND PLAY THERAPY INCREASE FRUIT AND VEGETABLE CONSUMPTION IN OBESE CHILDREN: CASE REPORT - Rohayati, Rohayati; Rekawati, Etty; Fitriyani, Poppy (Jurnal Keperawatan Respati Yogyakarta, 2021)
Fruit vegetable intake according to children's needs is very important to support optimal children's growth. Previous studies have shown that more than 80% of pre-school children are not getting an adequate intake of vegetables and fruits. Preliminary studies show that children's daily consumption of fruit vegetables is less than 1 serving. Family-based interventions with child development approaches are needed to increase the consumption of fruits and vegetables. Ten families with preschool children were recruited in this research using the purposive sampling technique. The inclusion criteria were active kindergarten students who were obese or overweight, lived in the Depok area, did not have chronic diseases or other health problems at the time of the study. The result shows that child's nutritional status is 80% obese and 20% overweight with an average body weight decrease from 34.3 kg to 33.2 kg. The obesity risk behavior show decrease in junk food consumption, sugary drink, formula milk, screen time and increase of adequacy fruit vegetable consumption from 0 % to 60%. The combination of family coaching interventions and play therapy can increase the portion of fruit and vegetable consumption in children and reduce the average weight of preschool children. Keywords: Family Coaching; Play Therapy; Obesity; Fruit Vegetable Consumption